Conservation biology of the rare and threatened Dryandra ionthocarpa, D. mimica and D. serra - Monks, Leonie T. (Curtin University, 1999)
The genus Dryandra, in the family Proteaceae, is endemic to south-western Australia. It consists of 92 named species and is an important component of some kwongan communities. Various aspects of the ecology of three threatened species of Dryandra (Dryandra ionthocarpa, D. mimica and D. serra) were studied. Threats to these species include weed invasion, inappropriate fire regimes, disturbance from roads, recreational activities, grazing, trampling, clearing and chemical drift from adjacent farms. Knowledge presented within on the ecology and biology of these three species is needed to develop appropriate conservation and management strategies.Population measurements of plant dimensions and seed bank size were assessed. Seed banks of all three species were shown to increase with increasing plant size. D. ionthocarpa and D. serra produced large numbers of viable seeds which was related to their mode of regeneration after fire. Experimental fires killed both species and seedling recruitment occurred following the death of adult plants. This indicated that both species are nonsprouters. D. mimica produced extremely small numbers of seeds, and had a high level of barren cones. Following an experimental burn, resprouting of adult plants was observed, but no seedling recruitment, indicating that this species is a resprouter.Granivore exclusion experiments showed that the seed banks of D. ionthocarpa and D. serra increased after the application of insecticide or bagging. Granivores are therefore considered to be a significant factor limiting the size of the seed bank. Timing of attack for D. ionthocarpa was shown to occur early in inflorescence development. However, the seed predators did not start to consume the seeds until after the infructescence was almost fully developed.Translocation studies were used to investigate whether D. ionthocarpa could survive and grow on other soil types or under the same edaphic conditions in other areas. Survival after nine months was better in spongolite or heavy clay soils. The highest survival and growth was for spongolite soils in a nature reserve near to the two known populations indicating that this species will grow well, at least initially in other areas, and that this area can be considered suitable for a larger' scale translocation. Reciprocal translocations were used to assess whether D. serra shows adaptation to local conditions across its distribution. No clear pattern was found, with only seedlings from the South Sister population surviving better at their original locality. Monitoring over a longer time period is recommended to assess whether a clearer pattern develops after flowering and fruiting.Plants of D. ionthocarpa with orange leaves were found to be under greater water stress during summer and autumn than green plants. The levels of chlorophyll a and b were also lower in orange plants in summer and autumn than green plants. These differences were attributed to a drought response, and the orange colour of this species during summer can therefore be used as an indicator of the health of the populations.An important objective of these investigations was to provide baseline information that could be used in the development of conservation and recovery strategies for these species. Several management actions are recommended. The health of the D. ionthocarpa populations should be assessed regularly using the orange foliage colour and total plant numbers as indicators. In the event the population is in decline the use of small scale controlled burns in autumn is recommended to stimulate seedling recruitment. This should be undertaken in conjunction with the control of seed predators pre-burn, and the watering of any seedlings recruited post-burn, for at least the first summer. In addition, translocation to other matched sites, particularly the spongolite soils of the Kalgan Plains Nature Reserve is recommended. No exclusion from fire is deemed necessary for D. mimica, as this species appears to tolerate fire. Active management of D. serra is not considered necessary, instead the species should be monitored regularly.